Pharmacogenomic analysis in patients with familial hypercholesterolemia - Hernandez, Carolina Dagli (2022)
Introduction: Familial hypercholesterolemia (FH) is a monogenic dyslipidemia with a high risk of developing early atherosclerotic disease. Statins are the first-line treatment of FH patients. Statins substantially reduce low-density lipoprotein cholesterol (LDL-c) and have a good efficacy and safety profile. However, some patients do not respond adequately whereas others experience statin-related adverse events (SRAE). Genetic and non-genetic factors contribute to the variability in the response to statins, but there are few studies on pharmacogenomic factors in the Brazilian population. Objective: To explore the association of genetic variants with the response to lipid-lowering drugs and SRAE in Brazilian FH patients Patients and Methods: Adult FH patients (n=114) were selected and clinical and pharmacotherapeutic data were obtained. The response to statin treatment was considered as LDL-c reduction of at least 50%. Blood samples were obtained for laboratory testing and genomic DNA extraction. A panel of 84 genes (related to HF and pharmacogenes) was analyzed by exon-targeted gene sequencing (ETGS). The DNA sequencing data was analyzed using a variant discovery pipeline. The functional impact of variants in pharmacokinetics (PK)- and pharmacodynamics (PD)-related genes was assessed using a functionality prediction score (FPS) and other in silico tools. LDL-c response to statin and SRAE risk was in carriers of deleterious variants in PK and PD genes, with minor allele frequency (MAF) > 5.0% or 10%, using univariate and multivariate linear regression analyses. Molecular modeling analysis was used to explore the functional effect in silico of deleterious variants. Results: Fifty-eight (50.8%) of the FH patients responded to statins and 24 (21.0) had SRAE. Obesity and alcohol consumption were more frequent in the non-responder (NRE) group (p<0.05), whereas the concomitant use of ezetimibe and SRAE were more prevalent in the responder (RE) group (p<0.05). The ETGS revealed 21 pathogenic variants in FH-related genes (19 LDLR, 1 APOB and 1 PCSK9), 402 variants in 23 PK-related genes (186 missense, 2 stop-gain, 1 stop-loss, 10 frameshift indel, 5 inframe deletions, 16 in splicing region, 29 in the 5´UTR region, and 153 in the 3´UTR region), and 752 variants in 33 PD-related genes (249 missense, 1 stop-gain, 9 start-loss, 5 frameshift indel, 9 inframe indel, 26 in splice-sites, 67 in the 5´UTR region, and 386 in the 3´UTR region). Functional prediction analysis revealed 21 missense, 1 stop-loss, 7 splice and 10 frameshift/inframe variants in PK genes are deleterious. Multivariate regression analysis of 16 variants in ABC and SLC transporters and CYP metabolizing enzymes with MAF > 10.0% and adjustment for non-genetic covariates, revealed that ABCC1 rs45511401 (c.2012G>T, p.Gly671Val) and SLCO1B3 rs60140950 (c.683G>C) increased LDL-c reduction to statin treatment (p<0.05). Molecular modeling analysis revealed that Val671 enhance the interaction of ABCC1 with statins compared with reference protein (Gly671). In PD-related genes, 93 missense, 1 start-loss, 3 stop-gain, 10 splice-site and 4 frameshift variants were predicted to be deleterious. The missense variant LPA rs76062330 (c.5468G>T) was associated with higher LDL-c reduction, even after corrections (Adjusted p=0.001). Multivariate linear regression analysis showed that the variant KIF6 rs20455 (c.2155T>C) reduced the LDL-c response to atorvastatin (p=0.014), whereas multivariate logistic regression revealed association of LPA rs3124784 (c.6046C>T) with increased response to statins (p=0.022). Deleterious variants in PK- and PD- related genes were not associated with increased risk of SRAE in FH patients. Conclusions: The deleterious variants ABCC1 c.2012G>T, SLCO1B3 c.683G>C, LPA c.5468G>T and LPA c.6046C>T enhanced LDL-c reduction in FH patients. KIF6 rs20455 (c.2155T>C), a neutral variant, decreased LDL-c reduction to atorvastatin. Deleterious variants in PK and PD genes were not associated with increased risk of SRAE.